Language Learning Strategies In English Fricative Consonants Through Arabic - Novita Wahidah; Sajidin Sajidin; Muhammad Aminuddin (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Many students face difficulties and lack confidence when it comes to English pronunciation, often doubting whether their pronunciation is correct. One significant challenge they face is the difference in dialect and pronunciation between their native language and the target language. In Indonesia, a Muslim-majority country, many students are familiar with Arabic, particularly in pesantren-based schools. Arabic and English share certain phonetic features, especially in the fricative consonant sounds, which could help Indonesian students learn English pronunciation more easily. This study explores how learning Arabic might aid in improving English pronunciation, specifically focusing on fricative sounds. Using a mixed-methods approach that combines both quantitative and qualitative data, this research applies a pre-experimental one-group pre-test and post-test design. The study involved fifteen junior high school students in grade VIII from an Islamic character school. The primary goal of the research was to assess how the students’ English pronunciation, particularly on fricative sounds, improved after learning Arabic. The results show a significant improvement in the pronunciation of /f/, /ʃ/, /s/, /z/, and /ʒ/ sounds. However, the students showed less improvement in the pronunciation of /ð/ and /θ/ sounds. This suggests that while Arabic may offer some advantages in mastering specific English sounds, there may be challenges that still hinder the improvement of other English consonants. These findings could provide insights into language learning strategies and the potential role of Arabic in enhancing English pronunciation.